Question
upstudy study bank question image url

Fill in the missing values to make the equations true. \[ \begin{array}{l}\text { (a) } \log _{7} 9-\log _{7} 2=\log _{7} \square \\ \text { (b) } \log _{3} \square+\log _{3} 5=\log _{3} 35 \\ \text { (c) }-4 \log _{9} 3=\log _{9} \square\end{array} \]

Ask by Henry Collins. in the United States
Nov 22,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \begin{array}{l} \text{(a) } \square = \frac{9}{2} \\ \text{(b) } \square = 7 \\ \text{(c) } \square = \frac{1}{81} \end{array} \]

Solution

To fill in the missing values in the equations, we can use the properties of logarithms. ### (a) We have the equation: \[ \log_{7} 9 - \log_{7} 2 = \log_{7} \square \] Using the property of logarithms that states \(\log_a b - \log_a c = \log_a \left(\frac{b}{c}\right)\), we can rewrite the left side: \[ \log_{7} \left(\frac{9}{2}\right) = \log_{7} \square \] This implies: \[ \square = \frac{9}{2} \] ### (b) We have the equation: \[ \log_{3} \square + \log_{3} 5 = \log_{3} 35 \] Using the property of logarithms that states \(\log_a b + \log_a c = \log_a (b \cdot c)\), we can rewrite the left side: \[ \log_{3} (5 \cdot \square) = \log_{3} 35 \] This implies: \[ 5 \cdot \square = 35 \] To find \(\square\), we divide both sides by 5: \[ \square = \frac{35}{5} = 7 \] ### (c) We have the equation: \[ -4 \log_{9} 3 = \log_{9} \square \] Using the property of logarithms that states \(k \log_a b = \log_a (b^k)\), we can rewrite the left side: \[ \log_{9} (3^{-4}) = \log_{9} \square \] This implies: \[ \square = 3^{-4} = \frac{1}{3^4} = \frac{1}{81} \] ### Summary of the missing values: \[ \begin{array}{l} \text{(a) } \square = \frac{9}{2} \\ \text{(b) } \square = 7 \\ \text{(c) } \square = \frac{1}{81} \end{array} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Let's solve each equation step by step to fill in the missing values. (a) Using the properties of logarithms, specifically the subtraction property, we can rewrite the equation: \[ \log_{7} 9 - \log_{7} 2 = \log_{7} \left( \frac{9}{2} \right) \] Thus, the missing value is: \[ \frac{9}{2} = 4.5 \] (b) Here, we apply the addition property of logarithms: \[ \log_{3} \square + \log_{3} 5 = \log_{3} (5 \cdot \square) \] We know from the equation that this must equal \(\log_{3} 35\): \[ \log_{3} (5 \cdot \square) = \log_{3} 35 \] To find \(\square\), we set \(5 \cdot \square = 35\): \[ \square = \frac{35}{5} = 7 \] (c) Using the property of logarithms regarding multiplication by a constant, we can rewrite the left-hand side: \[ -4 \log_{9} 3 = \log_{9} 3^{-4} \] Simplifying \(3^{-4}\): \[ 3^{-4} = \frac{1}{3^4} = \frac{1}{81} \] Thus, \[ \log_{9} \square = \log_{9} \left(\frac{1}{81}\right) \] The missing value is: \[ \frac{1}{81} \] In summary, the completed equations are: (a) \( \log_{7} \left( \frac{9}{2} \right) \) with missing value \( 4.5 \) (b) \( \log_{3} 7 \) with missing value \( 7 \) (c) \( \log_{9} \left(\frac{1}{81}\right) \) with missing value \( \frac{1}{81} \)

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy